Co-existence and switching between fast and Ω-slow wind solutions in rapidly rotating massive stars - Araya, I. (2018)
Most radiation-driven winds of massive stars can be modelled with m-CAK theory, resulting in the so-called fast solution. However, the most rapidly rotating stars among them, especially when the rotational speed is higher than ∼75 per cent of the critical rotational speed, can adopt a different solution, the so-called Ω-slow solution, characterized by a dense and slow wind. Here, we study the transition region of the solutions where the fast solution changes to the Ω-slow solution. Using both time-steady and time-dependent numerical codes, we study this transition region for various equatorial models of B-type stars. In all cases, in a certain range of rotational speeds we find a region where the fast and the Ω-slow solution can coexist. We find that the type of solution obtained in this co-existence region depends stongly on the initial conditions of our models. We also test the stability of the solutions within the co-existence region by performing base-density perturbations in the wind. We find that under certain conditions, the fast solution can switch to the Ω-slow solution, or vice versa. Such solution-switching may be a possible contributor of material injected into the circumstellar environment of Be stars, without requiring rotational speeds near critical values.